(untitled) (Raparin Journal of Humanities (RJH), 2023)
The article emphasizes the importance of identifying land uses and studying the natural environment as a critical stage in land use planning. and thus determining the most appropriate sites for the most appropriate uses to make good use of the, the study specifically examines the natural environment’s characteristics in the Sktan district, including its geology, topography, climate, soil, hydrology, natural vegetation, geomorphology, erosion, phenomena, and slope), because each of these phenomena has an impact on land use, furthermore, the article presents the Weighted Overlay model as a useful tool for generating land use maps and determining appropriate land use types.